Composition of the Essential oil of Endemic Helichrysum noeanum Boiss. (Asteraceae) Growing Wild in Turkey - Elkiran, Omer; Bagci, Eyup; Evren, Harun (Asian Journal of Chemistry, 2013)
Helichrysum genus is currently known and some are used in folk medicines. In Flora of Turkey, it is represented with 27 taxa, 15 of which are endemic to Turkey. Essential oil was obtained from the aerial parts of plant and yielded 0.1 % (v/w). The chemical composition of the essential oil obtained from Helichrysum noeanum was analyzed by GC and GC-MS system. Fourty one constituents were identified, representing 95.88 % of the total oil. gamma-Gurjunene (11.06 %), spathulenol (9.90 %), alloaromadendrene (7.53 %), beta-caryophyllene (7.10 %) are the major compounds determined in H. noeanum essential oil.
Keywords: Helichrysum noeanum; Asteraceae; GC-MS; Essential oil